Moral judgment in university students - Altez Rodríguez, Irma Susana (2003)
Development of Moral Judgment of 480 universitary students is presented according to their age, gender, and kind of university. James Rest’s Defining Issues Test (DIT) was applied for this research. Results show important differences among 17 to 22 years old students, and for gender, better female responses but no differences related to the kind of university. A scale based on percentiles is presented.